Medial gastrocnemius and soleus muscle‐tendon unit, fascicle, and tendon interaction during walking in children with cerebral palsy. (1st April 2017) - Barber, Lee; Carty, Chris; Modenese, Luca; Walsh, John; Boyd, Roslyn; Lichtwark, Glen
Abstract : Aim: This study investigates the in vivo function of the medial gastrocnemius and soleus muscle‐tendon units (MTU), fascicles, and tendons during walking in children with cerebral palsy (CP) and an equinus gait pattern. Method: Fourteen children with CP (9 males, 5 females; mean age 10y 6mo, standard deviation [SD] 2y 11mo; GMFCS level I=8, II=6), and 10 typically developing (6 males, 4 females; mean age 10y, SD 2y 1mo) undertook full body 3D gait analysis and simultaneous B‐mode ultrasound images of the medial gastrocnemius and soleus fascicles during level walking. Fascicle lengths were analysed using a semi‐automated tracking algorithm and MTUs using OpenSim. Statistical parametric mapping (two‐sample t ‐test) was used to compare differences between groups ( p <0.05). Results: In the CP group medial gastrocnemius fascicles lengthened during mid‐stance gait and remained longer into late‐stance compared to the typically developing group ( p <0.001). CP medial gastrocnemius fascicles shortened less during stance (1.16mm [SD 1.47mm]) compared to the typically developing group (4.48mm [SD 1.94mm], p <0.001). In the CP group the medial gastrocnemius and soleus MTU and tendon were longer during early‐ and mid‐stance ( p <0.001). Ankle power during push‐off ( p =0.015) and positive work ( p <0.002) and net work ( p <0.001) were significantly lower in the CP group. Interpretation: Eccentric action of the CP medial gastrocnemius muscle fascicles during mid‐stance walking is consistent with reduced volume and neuromuscular control of impaired muscle. Reduced ankle push‐off power and positive work in the children with CP may be attributed to reduced active medial gastrocnemius fascicle shortening. These findings suggest a reliance on passive force generation for forward propulsion during equinus gait. What this paper adds: Medial gastrocnemius fascicles in children with cerebral palsy (CP) contract eccentrically during mid‐stance phase. Soleus fascicles in CP and typical development function similarly during stance. The Achilles tendon contributes significantly to the stretch and shorten of the muscle‐tendon unit in CP and typical development. Reduced ankle power and work in CP may be attributed to reduced medial gastrocnemius fascicle shortening. This article is commented on by Schless et al. on pages781–782 of this issue.